Increased frequency of fibromyalgia among patients with chronic pain presenting to internal medicine clinics of a tertiary care hospital: a cross sectional study - Javed, Sana; Muhammad Zaid; Sumera Imran; Ayesha Hai; Patel, Muhammad Junaid (Journal of the Pakistan Medical Association, 2022)
Objective: To estimate the frequency of patients with fibromyalgia (by using the 2010 Modified Criteria for Fibromyalgia by American College of Rheumatology ( ACR ) presenting to Internal Medicine clinics Methods: A cross-sectional study conducted in the department of Internal Medicine, the Indus Hospital, khi, Pakistan between December 2016 and March 2018. Patients who visited internal medicine clinics, met the selection criteria, were included in the study. After taking informed consent patients were assessed for fibromyalgia according to the new 2010 Fibromyalgia Diagnostic criteria questionnaire. The patients were asked the questions in the national language, Urdu. Data analyzed using SPSS version 21. P value of < 0.05 was considered significant. Results: Of the 267 patients presenting to the internal medicine clinics and consenting for participating in the study 149 (55.80%) met at least one of the 2010 Fibromyalgia Criteria. The prevalence of fibromyalgia as estimated in this study was 56% with no difference in gender. Mean age of patients with fibromyalgia was 42.3 ± 14.6 and patients without fibromyalgia was 38.9 ± 13.7 which was statistically significant (p-value = 0.05, 10% level of significance). Of the 267 patient 197 (73.8%) were female and 70 (26.2%) were males, a male to female ratio of 1:2.81. Conclusion: All patients with generalized pain should be evaluated for fibromyalgia and a diagnosis made to reduce the cost of further referrals and investigations and delay in the management of this debilitating disorder. Keywords: Fibromyalgia, Chronic fatigue, Generalized Pain